Analisis Penerapan Akad Al-Ju’alah pada Perusahaan Multi Level Marketing: Studi atas Perusahaan HNI-HPAI - Rani Febriyanni; Marliyah Marliyah; Tuti Anggraini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This research is to find out whether the bonus given by PT. HNI-HPAI is in accordance with the ju'alah contract. The method in this study is a descriptive analysis method from personal studies on various information such as websites, desktop sites, and other social media. The research shows that PT HPAI adheres to a Multilevel Marketing business work system based on Islamic sharia. There is an element of service in the MLM system, meaning that a distributor sells goods that do not belong to him and he gets a wage from a percentage of the price of the goods and if he can sell according to the target he gets a bonus or gift set by the company. Bonuses or gifts in Islam are called al-jualah. Sell ​​is a wage or gift that has been promised to someone because he has done a job and the wage/gift can be given because the work that has been determined has been completed. According to the DSN fatwa NUMBER 62/DSNMUI/XII/2007 regarding the al-jualah contract, there are 5 conditions that must be considered by multi-level marketing companies, especially sharia-based MLM. PT. HNI-HPAI as a company that adheres to the MLM work system has met the requirements of the DSN fatwa. Keywords: MLM, ju'âlah, HNI-HPAI